2012
DOI: 10.1111/j.1442-200x.2011.03557.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biennial outbreak pattern of respiratory syncytial virus according to subtype (A and B) in the Zagreb region

Abstract: Over a 3 year period of observation, the biennial RSV cycle in Croatia cannot be explained by a difference in the predominant circulating subtype of RSV. Other unknown factors account for the biennial cycle of RSV epidemics in Croatia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Furthermore, the observation of 4 consecutive RSV A epidemics is at variance with previously reported time series [8-10,28] with pairs of epidemics of one group alternating between A and B. Nonetheless, our molecular analysis now extending to G variants within the group strains does support the previous observations by Mlinaric-Galinovic et al , 2009 and 2012 in Croatia that virus diversity does not appear to be the driver of the unusual epidemic patterns [32,33]. …”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, the observation of 4 consecutive RSV A epidemics is at variance with previously reported time series [8-10,28] with pairs of epidemics of one group alternating between A and B. Nonetheless, our molecular analysis now extending to G variants within the group strains does support the previous observations by Mlinaric-Galinovic et al , 2009 and 2012 in Croatia that virus diversity does not appear to be the driver of the unusual epidemic patterns [32,33]. …”
Section: Discussionsupporting
confidence: 61%
“…This cycle has been monitored over 17 consecutive years (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), and it was proved that the cycle repeats every 23-25 months and comprises 1 large or early and 1 small or late season. [26][27][28] Authors from Austria showed that HMPV outbreaks are also characterized by a biennial rhythm, with a strong peak of HMPV activity in late spring-summer months every second year. 13,17 In addition, they showed that HMPV outbreaks may overlap with RSV epidemics, but also can precede or follow annual RSV outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical samples from 1955 inpatients (aged 0–5 years) with acute respiratory tract infections were collected from January 1, 2006 to December 31, 2008 in the Zagreb region [Mlinaric‐Galinovic et al, 2012]. The study was conducted as part of the scientific projects nos.…”
Section: Methodsmentioning
confidence: 99%
“…HRSV was confirmed in 696/1,955 inpatients' nasopharyngeal secretions by detection with monoclonal antibodies, using a direct fluorescence assay (DFA‐Light Diagnostics, Chemicon International, Temecula, CA) at the Department of Virology, CNIPH. The virus group was determined by real‐time PCR [Mlinaric‐Galinovic et al, 2012]. Seventy‐two samples were chosen for sequencing, based on the collection dates of samples.…”
Section: Methodsmentioning
confidence: 99%